1996
DOI: 10.1021/jm9600508
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 3β-Aryl-8-azabicyclo[3.2.1]octanes with High Binding Affinities and Selectivities for the Serotonin Transporter Site

Abstract: A novel entry to tropane analogs of cocaine was developed based on the reaction of rhodium-stabilized vinylcarbenoids with pyrroles. These analogs were tested in binding to dopamine, serotonin (5-HT), and norepinephrine transporters in membranes from rat striatum and frontal cortex. In all the analogs, the aryl group at the 3 position was directly bound to the tropane ring and an ethyl ketone moiety was present at the 2 position. By appropriate modification of the aryl and nitrogen substituents, highly potent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 17 publications
5
67
0
Order By: Relevance
“…Previous studies had shown these aryl groups to contribute to the high potency and selectivity at SERT observed for the meperidine ethyl ester derivatives 2a-d (Table 1) as well as a variety of piperidine and tropane derivatives. 27-30 As illustrated in Scheme 1, an initial series of normeperidine derivatives 4 were prepared from the corresponding ethyl esters 2 using 1-chloroethyl chloroformate (ACE-Cl). This two-step one-pot processs typically afforded the normeperidine derivatives 4 in 59% - 73% yield.…”
Section: Chemistrymentioning
confidence: 99%
“…Previous studies had shown these aryl groups to contribute to the high potency and selectivity at SERT observed for the meperidine ethyl ester derivatives 2a-d (Table 1) as well as a variety of piperidine and tropane derivatives. 27-30 As illustrated in Scheme 1, an initial series of normeperidine derivatives 4 were prepared from the corresponding ethyl esters 2 using 1-chloroethyl chloroformate (ACE-Cl). This two-step one-pot processs typically afforded the normeperidine derivatives 4 in 59% - 73% yield.…”
Section: Chemistrymentioning
confidence: 99%
“…These reports now include diastereomeric excesses of up to 97% in the dirhodium(II) octanoate catalysed cyclopropanation of styrenes and vinyl ethers with (R)-pantolactone-and (S)-lactate-substituted vinyldiazomethane 18 with (Table 1) (Davies et al, 1993c(Davies et al, , 1997a These workers (Davies et al, 1998a) have shown that appropriate choice of vinyldiazo substituent allows facile subsequent transformation of the cyclopropyl products to 2,3-dihydrofurans with high asymmetric induction. This methodology has been extended to diene systems, furans (Davies et al, 1996b) to give 8-oxabicyclo[3.2.1]octan-3-ones and pyrroles (Davies et al, 1997b) to give tropanes (Scheme 4).The fundamental reaction sequence has allowed the preparation of the oxabicycles 20-22 and a series of 2β-acyl-3β-aryltropanes 23 (Davies et al, 1994a(Davies et al, , 1996c CCOO, as in catalysts 6 (substituents varied from H, Me, and Ph; to OH, NHAc, and CF 3 ) and Kennedy et al (1990) persued the chiral prolinate derivatives 7 (Z = H). They found that enantioselectivities in the cyclopropanation of styrene with ethyl diazoacetate were less than 12% ee and 30% ee respectively.…”
Section: Intermolecular Processesmentioning
confidence: 99%
“…The PET tracer [ 11 C] (+)-McN-5652-Z has been used for several years 11 , even though its low target to background ratio limits its use to high density regions like the midbrain 12,13 . A fluorine-18 labeled analog [ 18 Based on the observations of Carroll 19 and Davies 20,21 that selectivity for 5-HTT was enhanced by unsaturated substituents on the phenyl ring and by N-demethylation (trends confirmed by preliminary results with 4′-substituted analogs 22,23 ), we synthesized a series of 3′-substituted tropane analogs and measured their binding affinity towards the three monoamine transporters. The potency (Ki, nM) of the compounds was evaluated by competition against radiolabeled ligands selective for 5-HTT, DAT, and NET in rat forebrain tissue and human cell membranes and binding selectivity was calculated as the inverse ratio of Ki values.…”
Section: Introductionmentioning
confidence: 99%